Study of just retribution in the context of war crimes: An analysis from the perspective of command responsibility - Bermúdez-Bermúdez, Yonni Albeiro (DIXI, 2026)
This article will examine the relationship between just retribution in war crimes and command responsibility. Just retribution has emerged in international criminal law as a key guarantee for proportionally punishing conduct that violates human rights and international humanitarian law. Command responsibility holds criminally responsible superiors who, under their effective control, allow or facilitate subordinates to carry out conduct contrary to the law. This novel way of holding superiors liable highlights the obligation to prevent, supervise, and punish unlawful conduct committed within their sphere of control. Through an analysis of several emblematic cases and the jurisprudence of the International Criminal Tribunal for the former Yugoslavia, the theoretical and practical implications of just retribution in the punishment of superiors, who are often in privileged positions that facilitate the commission of atrocity crimes, were highlighted. Among the main findings, it is emphasized that a position of authority not only entails privileges, but also significant responsibilities and legal consequences in cases of non-compliance.